Application of hydrogen embritlement models to the blister growth behavior in 12Cr2MoNbVB steel and α -Fe exposed to low-energy D plasma - Nikitin, A.V.; Tolstolutskaya, G.D.; Ruzhytskiy, V.V.; Kopanets, I.E.; Karpov, S.A.; Vasilenko, R.L.; Rostova, G.Y.; Rybalchenko, N.D.; Sungurov, B.S. (Вопросы атомной науки и техники, 2017)
Processes of blisters and associated subsurface cracks nucleation during exposure of 12Cr2MoNbVB ferritic-martensitic steel and α-Fe under glow discharge hydrogen (deuterium) plasma with ion energies of ~ 1 keV and ion fluencies up to 2·10²⁴ D/м² at various temperatures have been examined. The methods used were scanning electron microscopy, thermal desorption spectroscopy and the D(³He, p)⁴He nuclear reaction. Temperature dependence of average blister diameter, the deuterium depth distribution and retention were studied. Application of hydrogen induced cracking models was considered to assess the effects of hydrogen from the plasma on the development of blisters and subsurface cracks. Based on this analysis, it is shown that significant crack growth rates can occur during reactor shut-down periods when the temperature of the structure decreases to less than about 373 K. Досліджено процеси розвитку блістерів і пов'язаних з ними підповерхневих тріщин, що виникають при впливі при різних температурах на 12Cr2MoNbVB феритно-мартенситну сталь і α-Fe водневої плазми тліючого розряду з енергією іонів ~ 1 кеВ і дозою ~ 2·10²⁴ D/м². Використано методи скануючої електронної мікроскопії, термодесорбції і ядерна реакція D(³He, p)⁴He. Отримано температурні залежності середнього діаметра блістерів, просторовий розподіл дейтерію в обсязі матеріалу і температурні інтервали його утримання. Вплив водню на розвиток блістерінга розглянуто із залученням моделей, розроблених для водневого охрихчення матеріалів. На основі цього аналізу зроблено висновок, що значні темпи зростання тріщин і блістерів можуть виникати під час періодів відключення реактора, коли температура конструкцій знижується до 373 K. Исследованы процессы развития блистеров и связанных с ними подповерхностных трещин, возникающих при воздействии при различных температурах на 12Cr2MoNbVB ферритно-мартенситную сталь и α-Fe водородной плазмы тлеющего разряда с энергией ионов ~ 1 кэВ и дозой ~ 2·10²⁴ D/м². Использованы методы сканирующей электронной микроскопии, термодесорбции и ядерная реакция (³He, p)⁴He. Получены температурные зависимости среднего диаметра блистеров, пространственное распределение дейтерия в объеме материала и температурные интервалы его удержания. Влияние водорода на развитие блистеринга рассмотрено с привлечением моделей, разработанных для водородного охрупчивания материалов. На основе этого анализа сделан вывод, что значительные темпы роста трещин и блистеров могут возникать во время периодов отключения реактора, когда температура конструкций снижается до 373 K.